OPTIMIZATION OF THERAPEUTIC MEASURES IN PREGNANT WOMEN WITH PYELONEPHRITIS - Галина Васильевна Былым; Оксана Владимировна Носкова; Елена Валерьевна Литвинова (The Publishing House Medicine and Enlightenment, 2024)
Objective to study the condition of the intrauterine fetus in pregnant women with chronic and gestational pyelonephritis and to evaluate the effect of ozone therapy on the main indicators of the fetoplacental system. Materials and methods. 98 pregnant women aged 29.50 ± 0.82 years with chronic and gestational pyelonephritis who were treated in the maternity ward of the Donetsk Clinical Territorial Medical Association for the period from 2020 to 2022 were examined. Depending on the therapy, the patients were divided into two main groups. Group I included 48 pregnant women who were prescribed a traditional treatment regimen for pyelonephritis. Group II included 50 pregnant women with pyelonephritis, in whom the traditional treatment regimen was supplemented with intravenous administration of ozonated saline solution. The control group consisted of 30 healthy pregnant women. Results. Before the start of treatment at 34-35 weeks of gestation, pregnant women in the study groups underwent an ultrasound examination of the mother-placenta-fetus system and identified calcifications, petrification, expansion of the intervillous space, polyhydramnios, oligohydramnios, fetal growth retardation syndrome, double contour of the fetal head and abdomen. After the treatment, there was an improvement in cardiotocographic parameters in women of group II under the influence of ozone therapy, which indicates positive changes in the state of the fetoplacental system - the total number and amplitude of decelerations decreased, and the number of fetal movements (10.6 ± 2.7) became closer to the control ( p > 0.05). All indicators of the biophysical profile of the fetus in women of group II with pyelonephritis who received ozone therapy did not differ significantly from the controls (p > 0.05) and acquired a statistical difference only in relation to the indicators of pregnant women of group I (p < 0.05). The use of medical ozone in the complex treatment of pyelonephritis contributed to a 2.0-fold decrease in the number of premature and pathological births by 2.1 and 1.6 times, respectively, cesarean section by 1.7 times and cases of fetal respiratory disorders syndrome by 2.1 times (p < 0.05) compared to pregnant women receiving traditional therapy. In newborns whose mothers received ozone therapy in the complex treatment of fetoplacental insufficiency against the background of pyelonephritis, perinatal CNS damage was observed 1.6 times less often (p < 0.05), the realization of intrauterine infection was 2.6 times less often (p < 0.05) than in newborns whose mothers received traditional treatment. Conclusions. The proposed complex of therapeutic and preventive measures has a positive effect on the activity of the mother-placenta-fetus systems, leads on average to a decrease in complications associated with gestation by 1.6-2.6 times. The inclusion of ozone therapy in the complex treatment of pregnant women with pyelonephritis helps to reduce the number of perinatal complications by 2.0 times compared with pregnant women who received a traditional set of therapeutic measures (p < 0.05).